Overexpression of UGPase and SPP genes in Nicotiana tabacum leaves causes accelerated plant development and increased biomass - Magdalena Rakoczy; Jan Podkowinski; Marek Figlerowicz (BioTechnologia)
Background Sucrose phosphate phosphatase (SPP) and uridine diphosphate-glucose pyrophosphorylase (UGPase) genes were overexpressed in Nicotiana tabacum to enhance the efficiency of the photosynthesis-related sucrose synthesis pathway, the primary route for incorporating newly fixed carbon into plant metabolism.